GREAT BRITAIN GOVERNMENTAL SYMBOLS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the prominent symbols that encapsulate the  essence of Great Britain's governance and rich history. It begins by examining the Royal  Coat of Arms, delving into its heraldic significance and the representation of England,  Scotland, and Ireland. The Crown Jewels are then spotlighted, emphasizing their role in showcasing regal magnificence and continuity. The Union Jack is celebrated as a visual  embodiment of the United Kingdom's unity, harmonizing the flags of England, Scotland,  and Ireland. The narrative extends to the architectural masterpiece, the Palace of  Westminster, highlighting its role as a symbolic powerhouse and the seat of British  democracy. Moving beyond visual symbols, the article explores the practical yet iconic  tradition of the red dispatch boxes, shedding light on their historical roots and enduring presence in government affairs. Additionally, it touches upon the Portcullis, revealing its significance as a symbol of parliamentary strength and security. This comprehensive exploration weaves together practical traditions, regal symbols, and architectural marvels, offering readers a nuanced understanding of the multifaceted elements that define Great Britain's governance